2009
DOI: 10.4038/cmj.v51i1.1371
|View full text |Cite
|
Sign up to set email alerts
|

Admission to medical schools in Sri Lanka: predictive validity of selection criteria

Abstract: Objective To assess the extent to which current selection criteria predict success in Sri Lanka's medical schools.Methods The study sample consisted of all students selected to all six medical schools in two consecutive entry cohorts. The aggregate marks of these students at the General Certificate of Education (GCE) Advanced Level examination, the district of entry, admission category, candidate type (school/private) and gender, were identified as entry point variables. Success in medical school was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 8 publications
6
17
0
2
Order By: Relevance
“…The article by Hewage et al [13] in the current issue shows the English placement test as a good predictor and furthermore agrees with de Silva et al [8] that A/L attempt (not more than two attempts) is a good predictor. It may not be such a debatable issue that students should not be selected for medicine if they had more than two attempts at A/L and that a test of English language should wholly or partially contribute to the z-score.…”
Section: Tests Of Cognitive Abilitiessupporting
confidence: 85%
See 1 more Smart Citation
“…The article by Hewage et al [13] in the current issue shows the English placement test as a good predictor and furthermore agrees with de Silva et al [8] that A/L attempt (not more than two attempts) is a good predictor. It may not be such a debatable issue that students should not be selected for medicine if they had more than two attempts at A/L and that a test of English language should wholly or partially contribute to the z-score.…”
Section: Tests Of Cognitive Abilitiessupporting
confidence: 85%
“…Rajapaksa commented that this study lacked information on some important predictors such as proficiency in English language, and the number of attempts at the A/L examination [7]. In a subsequent study by de Silva et al found that less than three A/L examination attempts was a strong predictor of success [8].…”
Section: Predictors Of Success During the Medical Careermentioning
confidence: 84%
“…Algumas vezes, este sonho se transforma em frustração, pois, ao se candidatar ao curso, o jovem se depara com uma realidade que constitui uma verdadeira barreira à realização da sua aspiração. Esta situação decorre das limitações impostas ao acesso ao curso na maioria das Faculdades de Medicina, quer na Europa [1][2][3][4] quer nos Estados Unidos [5][6][7] , decorrente do numerus clausus -expressão latina que significa número limitado (é um dos métodos usados para limitar o número de estudantes que têm acesso a um curso).…”
Section: Introductionunclassified
“…Os dados recolhidos correspondem a uma amostra obtida por intermédio de inquéritos de opinião. Os candidatos identificaram como principais razões de opção pelo curso de Medicina as seguintes: Altruísmo (mediana = 87,5);Vocação (mediana = 81,3); Influência Familiar (mediana = 75,0); Prestígio Social (mediana = 75,0); …”
unclassified
“…[1][2][3][4] Consequently, all medical schools have in recent years evaluated and adapted their selection criteria and processes. [5,6] Most South African (SA) medical schools use academic and non-academic criteria to select students, the former accounting for 70 -80% of admission requirements.…”
Section: Introductionmentioning
confidence: 99%